Diretrizes para o gerenciamento de resíduos de equipamentos eletroeletrônicos. Estudo de caso : Uberaba, MG - Rajovic, Katia da Costa Sousa (Universidade Federal de São Carlos, 2016)
The waste electrical and electronic equipment (WEEE) is a sort of waste that has been experiencing significant arising in its generation rates, consisting of a great challenge to decision makers and to society as a whole when it comes to its management. Toxic substances found in WEEE components are also reason of concern. Thus, the correct disposal of WEEE is essential. In Brazil the law 12.305/2010, the National Solid Waste Policy (NSWP) features the correct destination for WEEE, which now have to be included in reverse logistics systems, taking into consideration all the agents of the generation of WEEE process. Therefore, the aim of this study was to develop a general guideline for the management of WEEE, considering the shared responsibility for the waste, having as a study case the city of Uberaba, Brazil. To reach the aim of this study data was collected from different agents that deal with WEEEs, such as retailers, technical assistance companies, cooperatives and other organizations that receive or give a destination to such waste. It has not been possible to estimate the exact amount of WEEE generated in the visited places, once the respondents have no form of monitoring these amounts. However, it has been possible to identify forms of destination of the waste, and the informal sector was shown to be a frequent option for that purpose. It has also been possible to note that most of the interviewed persons have no knowledge regarding the NSWP nor are taking part in actions aiming the development of reverse logistics programs. Suggestions were listed in the end of the work, hoping to contribute towards future programs for WEEE management, taking into consideration the situation observed and other studies developed by others about the subject.
Keywords: Gestão de resíduos; Resíduos de equipamentos eletroeletrônicos; Logística reversa; Waste management; Waste of electrical and electronic equipment; Reverse logistics; ENGENHARIAS